Commercially available transfection reagents and negative control siRNA are not inert - Kleefeldt, Jan M.; Pozarska, Agnieszka; Nardiello, Claudio; Pfeffer, Tilman; Vadász, István; Herold, Susanne; Seeger, Werner; Morty, Rory E. (Analytical biochemistry, 2020)
The transfection of synthetic small interfering (si)RNA into cultured cells forms the basis of studies that use RNA interference (commonly referred to as “gene knockdown”) to study the impact of loss of gene or protein expression on a biological pathway or process. In these studies, mock transfections (with transfection reagents alone), and the use of synthetic negative control (apparently inert) siRNA are both essential negative controls. This report reveals that three widely-used transfection reagents (X-tremeGENE™, HiPerFect, and Lipofectamine® 2000) and five commercially-available control siRNA (from Ambion, Sigma, Santa Cruz, Cell Signaling Technology, and Qiagen) are not inert in cell-culture studies. Both transfection reagents and control siRNA perturbed steady-state mRNA and protein levels in primary mouse lung fibroblasts and in NIH/3T3 cells (a widely-used mouse embryonic fibroblast cell-line), using components of the canonical transforming growth factor-β signaling machinery as a model system. Furthermore, transfection reagents and control siRNA reduced the viability and proliferation of both lung fibroblasts and NIH/3T3 cells. These data collectively provide a cautionary note to investigators to carefully consider the impact of control interventions, such as mock transfections and control siRNA, in RNA interference studies with synthetic siRNA.
Gesehen am 03.12.2020